J. PEZEL’S MUSIC FOR THE ENSEMBLE OF COPPER WIND INSTRUMENTS IN THE CONTEXT OF GERMAN TRADITION OF 17th CENTURY - SLUPSKYI, Victor (Studia Universitatis Babes-Bolyai Musica, 2022)
The creative activity of Johann Pezel, the then-known multiinstrumentalist, whose creative path and kind of activity reflects the life and status of the musician of the Baroque era, is analyzed in the article in the context of the development of the German ensemble performance on copper wind instruments of the 17th century. It is noted that the motivation for the appearance of works for the ensemble of copper wind was a purely practical need to replenish the repertoire of urban performers. The works are written considering the technical capabilities of the instruments and follow the specifics of the genre-style tendencies of German instrumental music of the 17th century. The subject matter and methods of analysis should be distributed to the composer’s work of J. Pezel’s contemporaries, who also created music for the ensemble of copper brass, and to include their works in the repertoire of current performers.